A novel GA optimized SHE PWM hybrid cascaded H-bridge multilevel inverter with capacitor voltage averaging for motor drive applications - Routray A.; Patel V.; Mahanty R.; Singh R.K. (My University, 2025)
This paper proposes a new hybrid cascaded multilevel inverter (HCMLI) using selective harmonic elimination pulse width modulation (SHE-PWM) that synthesizes an eleven level output voltage with two dc sources and a pre-charged capacitor using twelve switches, in contrast to conventional twenty switches and five dc sources. Genetic algorithm (GA) has been used to compute switching angles of the HCMLI in this work. The proposed optimized HCMLI using SHE-PWM enables capacitor charge balance through an averaging scheme to reduce the steady state voltage error of the capacitor. The optimal structure for the proposed topology has been investigated for objectives such as minimum number of switches and lesser number of dc voltage sources for producing maximum output voltage steps. © 2016 IEEE.